An Olive-Derived Extract 20% Rich in Hydroxytyrosol Prevents β-Amyloid Aggregation and Oxidative Stress, Two Features of Alzheimer Disease, via SKN-1/NRF2 and HSP-16.2 in Caenorhabditis elegans - Jose M. Romero-Márquez; María D. Navarro-Hortal; Victoria Jiménez-Trigo; Pedro Muñoz-Ollero; Tamara Y. Forbes-Hernández; Adelaida Esteban-Muñoz; Francesca Giampieri; Irene Delgado Noya; Pedro Bullón; Laura Vera-Ramírez; Maurizio Battino; Cristina Sánchez-González; et al. (MDPI AG, 2022)
Olive milling produces olive oil and different by-products, all of them very rich in different bioactive compounds like the phenolic alcohol hydroxytyrosol. The aim of the present study was to investigate the effects of an olive fruit extract 20% rich in hydroxytyrosol on the molecular mechanisms associated with Alzheimer disease features like Aβ- and tau- induced toxicity, as well as on oxidative stress in Caenorhabditis elegans. Moreover, characterization of the extracts, regarding the profile and content of phenolics, as well as total antioxidant ability, was investigated. The study of lethality, growth, pharyngeal pumping, and longevity in vivo demonstrated the lack of toxicity of the extract. One hundred μg/mL of extract treatment revealed prevention of oxidative stress and a delay in Aβ-induced paralysis related with a lower presence of Aβ aggregates. Indeed, the extract showed the ability to avoid a certain degree of proteotoxicity associated with aggregation of the tau protein. According to RNAi tests, SKN-1/NRF2 transcription factor and the overexpression of HSP-16.2 were mechanistically associated in the observed effects.